2017
DOI: 10.5539/jas.v9n12p160
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Insect Pests and Plant Diseases to Changing and Variable Climate: A Review

Abstract: Natural and anthropogenic factors have resulted in altered environmental conditions that influence changes in abundance and diversity of insect pests. Global climate change projections focus on crop yields and adaptation strategies to declining yields and ignore the likely impact of a changing climate on insect pests and plant diseases. In this research paper, we review the effects of climate variables namely temperature, carbon dioxide (CO 2 ), precipitation and extreme weather events on insect pests and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Several bioclimatic indices have been proposed for estimating the risk of moisture-induced diseases, which showed that areas displaying a Mediterranean-like climate would tendentiously present low risks of contamination, particularly in southern Europe (Fraga et al 2013;Calonnec et al 2017). While drier environments may lead to higher insect and viral outbreaks, wet periods are expected to trigger cryptogamic and bacterial diseases, which can indirectly disturb population dynamics of insect pests (Katsaruware-Chapoto et al 2017). In fact, current research suggests that mildews remains the Fig.…”
Section: Viticultural Climatic Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bioclimatic indices have been proposed for estimating the risk of moisture-induced diseases, which showed that areas displaying a Mediterranean-like climate would tendentiously present low risks of contamination, particularly in southern Europe (Fraga et al 2013;Calonnec et al 2017). While drier environments may lead to higher insect and viral outbreaks, wet periods are expected to trigger cryptogamic and bacterial diseases, which can indirectly disturb population dynamics of insect pests (Katsaruware-Chapoto et al 2017). In fact, current research suggests that mildews remains the Fig.…”
Section: Viticultural Climatic Indicesmentioning
confidence: 99%
“…Moreover, existing pests are likely to expand, as well as invasion by new insect pests as a consequence of the foreseen increased frequency of extreme weather events, temperature, carbon dioxide levels, and changes in moisture conditions (Jaworski and Hilszczański 2013). However, an accurate quantification of the potential impact of climate change on biotic stresses represents an important challenge, since pest and host responses to environmental shifts are highly variable and complex (Katsaruware-Chapoto et al 2017).…”
Section: Viticultural Climatic Indicesmentioning
confidence: 99%
“…Natural and anthropogenic factors have resulted in altered environmental conditions that influence changes in abundance and diversity of insect pests [22], which then possibly affect the intensity and frequency of pest outbreaks on host plants [23]. The C. camphora-hosted insect pest outbreak dataset that was compiled are multi-proxy datasets of pest complexes on camphor trees.…”
Section: Pest Cumulative Characteristicsmentioning
confidence: 99%
“…Most of the respondents showed low disease in OP crops in hills (56) and terai (26) than in hybrids (6 and 9 in hills and terai, respectively). In terai, plants are more susceptible to insect pests due to high temperatures, high rainfall, high humidity, and saturated field conditions, which create favorable conditions for the infestation (Katsaruware et al, 2017).…”
Section: Plant Protectionmentioning
confidence: 99%